1986
DOI: 10.1002/tea.3660230407
|View full text |Cite
|
Sign up to set email alerts
|

The effects of teachers' wait‐time and knowledge comprehension questioning on science achievement

Abstract: The purpose of this experimental study was to investigate the effects of varied teacher wait‐time durations and cognitive questioning levels on student achievement. Thirty preservice teachers taught a science lesson in which the length of wait‐time and percentage of high and low cognitive questions were prescribed. The lessions were audio‐taped to insure fidelity to the scripted lessons. At the end of the lesson a criterion referenced test was administered. The results of this test were used as the dependent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…In summary, attempts to show a relationship between student achievement and certain types or cognitive levels of teacher questions have been inconclusive (Chin, 2007). Although there are some correlational studies showing positive relationships between certain types of teacher questions and student achievement (Gall, 1970;Rosenshine, 1971), experimental studies have been unable to establish causal linkages (Riley, 1986;Carlsen, 1991;Chin, 2007).…”
Section: Relationships Between Question-ing and Student Achievementmentioning
confidence: 99%
“…In summary, attempts to show a relationship between student achievement and certain types or cognitive levels of teacher questions have been inconclusive (Chin, 2007). Although there are some correlational studies showing positive relationships between certain types of teacher questions and student achievement (Gall, 1970;Rosenshine, 1971), experimental studies have been unable to establish causal linkages (Riley, 1986;Carlsen, 1991;Chin, 2007).…”
Section: Relationships Between Question-ing and Student Achievementmentioning
confidence: 99%
“…Additionally, the amount of time that adults talk is decreased (Riley, 1986;Skinner, Fletcher, & Henington, 1996).…”
Section: Fosters Improved Linguistic Responsesmentioning
confidence: 99%
“…Collaboration among children in the classroom is encouraged (Maroni, 2011), particularly because more children tend to verbally participate (Tobin, 1986). In general, more significant educational benefits accrue from silences extending beyond 3 seconds (Altiere & Duell, 1991;Maroni, 2011;Riley, 1986).…”
Section: Nourishes Contemplative and Speculative Thinkingmentioning
confidence: 99%
“…Previous research on wait time identified a 3-second threshold after asking higher cognitive level questions (Boeck & Hillenmayer, 1973;Edwin, 1999;Jones, 1980;Matthiesen, 2006;Swift & Gooding, 1983;Riley, 1986;Tobin, 1986). Jones (1980) reported 2.8 seconds of wait time for convergent questions, whereas the average time for divergent questions was 6.9 seconds in a middle school science classroom.…”
Section: Discussionmentioning
confidence: 99%
“…We will be using the wait-time defined as "the pause following any teacher utterance and preceding any student utterance" (Tobin, 1987, p.90). Research has shown that when the average wait time was at least 3 seconds or more, student achievement was enhanced (Riley, 1986;Rowe, 1978;Tobin, 1986). Three seconds or more are considered optimal for students to formulate a well-thought out response (Rowe, 1974;Stahl, 1994;Tobin, 1986).…”
Section: Introductionmentioning
confidence: 99%